ASSESSMENT OF THE TECHNICAL CONDITION OF ELECTRICAL EQUIPMENT IN MOBILE ROBOTIC COMPLEXES USING FUZZY CLASSIFICATION - A.V. Zayara; V.P. Fandeyev (Надежность и качество сложных систем)
Background. Modern mobile robotic complexes are equipped with sophisticated electrical equipment, which causes more than half of the failures caused by degradation processes. To ensure the restoration of the complexes' operability, the development of a new maintenance and repair system is required. Materials and methods. An approach to assessing various gradations of the technical condition of electrical equipment of mobile robotic complexes using a fuzzy classification is considered. It is proposed to integrate elements of the proactive concept into the existing scheduled preventive maintenance and repair system, which involves continuous monitoring of the technical condition according to a generalized parameter to determine the moment of occurrence of a potential failure condition. Fuzzy inference is used to solve this problem. Results and conclusions. Confirmation of the need for repair effects is made by probabilistic assessment of the current class of technical condition.